PERAN LMI DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MISKIN MELALUI PROGRAM GADUH TERNAK BAROKAH DI KABUPATEN TRENGGALEK - Diah Ayu Wulanda; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Gaduh Ternak Barokah is a program established by the Infaq Management Institute to empower the poor who have the ability to raise livestock to meet their daily needs. This program is a collaboration between breeders and the Infaq Management Institute where capital is provided in the form of livestock, namely goats. Breeders row livestock with their own energy and the ability to raise livestock only and later the results of animal husbandry were divided according to mutual agreement. This Gaduh Ternak Barokahis programmed to the economically disadvantaged society of Banaran, Depok Village, Bendungan suburb, Trenggalek Regency. This research aims at determining the role of Gaduh Ternak Barokah program on alleviating the poor society of Banaran, Depok Village, Bendungan suburb, Trenggalek regency based on prosperity indicators. The research approach is qualitative descriptive and uses a case study strategy. The informants in this study consisted of those who received assistance from the program, namely farmers. The technique of determining informants in this study used purposeive sampling techniques and data collection techniques were carried out through interviews and direct observation. Based on the research result, it is shown that Gaduh Ternak Barokah has a role on improving the farmers’ wealth in the point of view of prosperity.Keywords: Role, Empowerment, Farmers, Animal Husbandry ProgramREFFERENCESAl-Utsaimin, Muhammad Shalih. 2012. Ensiklopedi Zakat. Jakarta: Pustaka as-SunnahAsh-Shiddieqy, M Hasbi. 2012. Pedoman Zakat.  Semarang: PT Pustaka Rizki PutraAsnaini, Zakat Produktif dalam Perspektif Hukum Islam, (Yogyakarta: Pustaka Pelajar, 2008), h 50___________________.Zkat Produktif dalam Perspektif Hukum Islam, (Yogyakarta: Pustaka Pelajar, 2008), h 63Badan Pusat Statistik. 2017. Profil Kemiskinan di Indonesia September 2013-2016. Berita Resmi Statistik, (Online), (http://bps.go.id/brs/view/id/1099 diakses tanggal 20 Mei 2019).Badan Pusat Statistik. 2017. Jumlah Penduduk Miskin, Persentase Penduduk Miskin dan Garis Kemiskinan di Jawa Timur 2013-2016. Kemiskinan, (Online), (http://www.bps.go.id/linkTabelStatis/view/id/1494, diakses tanggal 28 Mei 2019).Badan Pusat Statistik. 2017. Profil Kemiskinan di Trenggalek September 2016. Berita Resmi Statistik, (Online), (http://bps.go.id/Brs/view/id/1227, diakses tanggal 28 Mei 2019).Gulo, W. 2002. Metodologi Penelitian. Jakarta: Penerbit PT. Grasindo.Hadi, AgusPurbathin. 2004. KonsepPemberdayaan, Partisipasi dan Kelembagaan dalam Pembangunan.Yayasan Agribisnis/Pusat Pengembangan Masyarakat Agrikarya (PPMA).Hafidhuddin, Didin. 2004.  Zakat Dalam Perekonomian Modern. Jakarta: Gema InsaniHikmat, Harry.2010. Strategi Pemberdayaan Masyarakat. Bandung: Humaniora Utama PressKamus Besar Bahasa Indonesia Esidi 3. 2007. Departemen Pendidikan Nasional. Balai PustakaMiftah, A. A. 2008. Pembaharuan Zakat untuk Pengentasan Kemiskinan di Indonesia. Innovatio (Online), Vol. VII, No. 14, (http://i-epistemology.net/v1/attachments/1137inv7n14%20Pembaharuan%20Zakat2untuk%20Pengentasan%20Kemiskinan%20di%20Indonesia%20%20A.A.%20Miftaf.pdf, diakses tanggal 27 Mei 2019).Mahendrawaty, Nanih. 2001. Pembangunan Masyarakat Islam dariIdeologi, strategi, sampai Tradisi. Jakarta: Remaja Rosda Karya.Moleong, Lexy J. 2001. Metodologi Penelitian Kualitatif. Edisi Revisi. Bandung: Remaja Rosda Karya._______________. 2010. Metodologi Penelitian Kualitatif. Edisi Revisi. Bandung: Remaja Rosda Karya.Permana, Trisna Setia. 2016. Peran Pertanian Urban pada Kesejahteraan Petani Muslim Ditinjau dari Perspektif Islam (Studi pada Empat Kelompok Tani di Surabaya). Skripsi tidak diterbitkan. Surabaya Ekonomi dan Bisnis Universitas Airlangga.Qardawi, Yusuf. 2011. Hukum Zakat. Bogor: Pustaka Litera AntarNusaBalai PustakaQardhani, Yusuf. 2006. Kiat Islam Mengentaskan Kemiskinan. Jakarta: GemaInsani Pers.Ryandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (Zakat, Infaq, Shadaqah, dan Waqaf). Surabaya: Ifdi dan Cenforis.Sabiq, Sayyid. 2008. Fikih Sunnah.. Jakarta: Cakrawala PublishingSoekanto, soerjono, Sosiologi Suatu Pengantar, Jakarta; MizanSomantri, Gumilar Rusliwa. 2005. Memahami Metode Kualitatif. Makara, Sosial Humaniora, Vol. 9 No. 2, Desember 2005: 57-65. Depok: Universitas Indonesia.Sudibyo, Bambang. 1998. Kemiskinan di Indonesia. Bandung :Mirzan.Sugiyono. 2009. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Sulistiani, AmbarTeguh. 2004. Kemitraan Dan Model-model Pemberdayaan. Jogjakarta: Gava Media.Sumodiningrat, Gunawan. 1999. PemberdayaanMasyarakat Dan JPS. Jakarta: Gramedia.Republik Indonesia. Undang-Undang RI Nomor 23 Tahun 2011 tentang Pengelolaan Zakat (Diakses dari http://dki.kemenag.go.id/index.php?a=artikel&id=14625&t=2646 tanggal 27 Juni 2019).Yin, Robert K.2012.Studi Kasus:Desain dan Metode. Jakarta: PT Raja Grafindo Persada.Yulizar D. danMoch.Tufik. 2016. Fiqih Tamkin (Fiqih Pemberdayaan) :Membangun Modal Sosial Dalam Mewujudkan Khairu Ummah. Jakarta. Qisthi Press.Zuhayly, Wahbah Al. 2008. Zakat Kajian Berbagai Mazhab. Bandung: PT Remaja Rosdakarya.